An improved quantum key distribution protocol for verification. (19th May 2019) - Kumar, Ankit; Dadheech, Pankaj; Singh, Vijander; Poonia, Ramesh C.; Raja, Linesh
Abstract: Facts say that practical cryptographic systems are now within the range. Quantum cryptography generally gives the solution which uses the various methods of polarization to leave the transmitted data undisturbed. In this work we try to improve the data security by increase the key size shared between parties involved used in quantum cryptography. Quantum cryptography uses storing the split particles involved and then measuring them and creating what they use, eliminating the problem of unsafe storage.